2014
DOI: 10.1142/s0129167x14500827
|View full text |Cite
|
Sign up to set email alerts
|

A Kadison–Kastler row metric and intermediate subalgebras

Abstract: In this paper we introduce a row version of Kadison and Kastler's metric on the set of C*-subalgebras of B(H). By showing C*-algebras have row length (in the sense of Pisier) of at most 2 we show that the row metric is equivalent to the original Kadison Kastler metric. Ino and Watatani have recently proved that in certain circumstances sufficiently close intermediate C*-algebras occur as small unitary perturbations. By adjusting their arguments to work with the row metric we are able to obtain universal consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The author and Watatani [12] showed that for an inclusion of simple C * -algebras C ⊆ D with finite index in the sense of Watatani [23], sufficiently close intermediate C * -subalgebras are unitarily equivalent. The implementing unitary can be chosen close to the identity and in the relative commutant algebra C ′ ∩ D. Our estimates depend on the inclusion C ⊆ D, since we use the finite basis for C ⊆ D. Dickson obtained uniform estimates independent of all inclusions in [10]. To get this, Dickson showed that row metric is equivalent to the Kadison-Kastler metric.…”
Section: Introductionmentioning
confidence: 99%
“…The author and Watatani [12] showed that for an inclusion of simple C * -algebras C ⊆ D with finite index in the sense of Watatani [23], sufficiently close intermediate C * -subalgebras are unitarily equivalent. The implementing unitary can be chosen close to the identity and in the relative commutant algebra C ′ ∩ D. Our estimates depend on the inclusion C ⊆ D, since we use the finite basis for C ⊆ D. Dickson obtained uniform estimates independent of all inclusions in [10]. To get this, Dickson showed that row metric is equivalent to the Kadison-Kastler metric.…”
Section: Introductionmentioning
confidence: 99%